Research on the factors affecting the adoption of health short videos by the college students in China: unification based on TAM and UTAUT model - Han, Pu; Liu, Senling; Zhang, Deqiang; Li, Xiong; Li, Xiaoyan (Frontiers in Psychology, 2025)
BackgroundHealth short videos, as an emerging mode of information dissemination, play a crucial role in enhancing health awareness and promoting healthy behavior among college students. It is crucial to optimize both the content and dissemination strategies of these videos to amplify their impact on health communication and to enhance the health literacy of this demographic.ObjectiveThis study aims to construct a comprehensive model to explore the key factors influencing the use of health short videos among Chinese college students, including perceived usefulness, perceived ease of use, and performance expectations, among other factors. The goal is to supply theoretical foundations and practical guidance for optimizing health short video content and dissemination strategies, thereby enhancing college students’ health literacy and quality of life.MethodsAn online survey was conducted among Chinese college students to investigate their inclination to acquire health information from health short videos. Based on TAM and UTAUT frameworks, a model was constructed to examine the factors influencing college students’ adoption of health information from health short videos. Through structural equation modeling, the study analyzed the impact of health short videos on the information adoption behavior of college students.ResultsThis study included a total of 296 Chinese college students. Results from the structural equation model indicated that perceived usefulness (β = 0.443, p < 0.001), perceived ease of use (β = 0.398, p < 0.001), performance expectancy (β = 0.434, p < 0.001), effort expectancy (β = 0.456, p < 0.001), social influence (β = 0.443, p < 0.001), information quality (β = 0.427, p < 0.001), and perceived trust (β = 0.482, p < 0.001) significantly positively influenced intention to adopt health short videos. Conversely, perceived risk (β = −0.415, p < 0.001) and perceived disease threat (β = −0.480, p < 0.001) had significant negative effects on adoption intention. Additionally, facilitating conditions (β = 0.421, p < 0.001) positively influenced adoption behavior, and adoption intention significantly affected adoption behavior (β = 0.406, p < 0.001).ConclusionThe adoption of health short videos by Chinese college students is primarily positively influenced by factors such as perceived usefulness, ease of use, performance expectancy, effort expectancy, social influence, information quality, and trust. Conversely, perceived risk and disease threat negatively affect their usage. Therefore, to promote college students’ continuous attention to and adoption of health short videos, the quality and credibility of health short videos should be improved, the user interface design should be optimized, usability should be enhanced, and social influence strategies should be used to enhance the attractiveness and persuasiveness of health information.